Abdusselâm el-'Uceylî'nin Edebî Kişiliği ve Bâsime Beyne'd-Dumû' Adlı Eseri - Hazer, Dursun (Dinî araştırmalar, 2004)
Abdussalam al-Ucayli is one of the important story writers and novelist of Syria. Together with committing to the Arap-Islâm values, he is also the litterateur who benefits from universal values and writes in this direction. This novel named Bâsima bayna’d-Dumu‘ is his first essay; he also benefited from his own life story while he was writing this. In this novel he investigated young Syrian intellectuals expectations from life in 1950s, their hopes, their hopelesnes, they face to face in modern life and depressions with which they confrent